2021
DOI: 10.5539/ies.v14n10p65
|View full text |Cite
|
Sign up to set email alerts
|

Digital Assessment Literacy: The Need of Online Assessment Literacy and Online Assessment Literate Educators

Abstract: Creation of reliable online assessments have always been a concern by educators, this research article provides an idea for providing professionals training development for creating online assessments for the inexperienced assessment literate teachers. The research has placed the importance on the training of the educators in the assessment literacy with a proposed model of utilization of Educational framework to create digital online assignments using IT integrated tools. This paper uses mixed method research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In addition, it is not only the teachers that should have sustainable knowledge in utilizing technology and instructional media for online teaching but students must also possess skills in using the technology for their learning. This finding agrees to findings of Husain (2021) who asserted that educators need to be trained as the assessment literate educators, with the integration of information communication technology tools. Moreover, teachers' and students' experience in using technology became an opportunity in an online assessment (Yulianto & Mujtahid, 2021).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it is not only the teachers that should have sustainable knowledge in utilizing technology and instructional media for online teaching but students must also possess skills in using the technology for their learning. This finding agrees to findings of Husain (2021) who asserted that educators need to be trained as the assessment literate educators, with the integration of information communication technology tools. Moreover, teachers' and students' experience in using technology became an opportunity in an online assessment (Yulianto & Mujtahid, 2021).…”
Section: Resultssupporting
confidence: 90%
“…In their analysis, Cundell & Sheepy (2018) reported that students in online learning were drawn to the flexibility of being able to complete course work at any time anywhere and being able to make it fit into their schedules. This is supported by Husain (2021) who asserted that educators need to be trained as the assessment literate educators, with the integration of information communication technology tools. In addition to the above mentioned studies, Yulianto & Mujtahid (2021) conducted a qualitative study in Indonesia where majority of the participants claimed that the online assessment helped educators assessing students' achievement during the Covid-19 situation.…”
Section: Teachers' Perspective In Online Writing Assessmentmentioning
confidence: 99%
“…According to the findings of studies by Husain (2021), there have been many instances of illiteracy among children of oil palm plantation workers since the Malaysian government banned Indonesian students from attending schools there, which has been made worse by the lack of adequate educational infrastructure [on the Indonesian Malaysian border]. The research by Yanti et al (2022), which found that there are still very few academic and teacher infrastructures in the area of the Indonesia-Malaysia cross-border post (especially in Sambas Regency), supports this.…”
Section: Resultsmentioning
confidence: 99%
“…Digital libraries can facilitate lecturers to respond faster to the development of science (Borgman, 2006 ;Ross, 2012) because they can collaborate in creating a good climate of self-development (Hyman et al, 2014;Naidoo, 2020) and a manifestation of a critical and creative attitude towards the development of technology and information in the world (Chowdhury, 2002;Husain, 2021;Manurung, Purwadi, & Sugiharto, 2022). Digital libraries are also a solution to the difficulty of lecturers getting hard-copy references to books and articles to complete scientific papers (Bainbridge et al, 2008;Kim, 2018;Panezi, 2014;Widyasari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%